The Effect of 17β-Estradiol Administration on Cutaneous Wound Healing in 24-Week Ovariectomized Female Mice. (21st January 2014) - Mukai, Kanae; Nakajima, Yukari; Urai, Tamae; Komatsu, Emi; Takata, Kana; Miyasaka, Yuriko; Nasruddin,; Sugama, Junko; Nakatani, Toshio
Abstract : Estrogen replacement promotes cutaneous wound healing in 8–10-week young ovariectomized female mice. However, research using aged ovariectomized female mice has not been reported, to the best of our knowledge. Therefore, we investigated the effect of 17 β -estradiol on cutaneous wound healing using 24-week middle-aged ovariectomized female mice. Twenty-week-old female mice were divided into three groups: medication with 17 β -estradiol after ovariectomy (OVX + 17 β -estradiol), ovariectomy (OVX), and sham (SHAM). After 4 weeks, the mice received two full-thickness wounds. Then, the OVX + 17 β -estradiol group was administered 17 β -estradiol at 0.01 g/day until healing. The ratio of wound area in the OVX + 17 β -estradiol group was significantly decreased compared with that in the OVX group. The numbers of neutrophils and macrophages in the OVX + 17 β -estradiol group were significantly smaller than those in the OVX group. In addition, the ratio of myofibroblasts in the OVX + 17 β -estradiol group was significantly higher than that in the OVX group. These data suggested that exogenous continuous 17 β -estradiol administration promotes cutaneous wound healing in 24-week OVX female mice by reducing wound area, shortening inflammatory response, and promoting wound contraction. However, it is unclear whether the effect of exogenous estrogen on wound healing outweighs the delay of wound healing due to advanced age.